Influence of the Asian crisis on the Peruvian industry - Sandoval Incháustegui, César (1998)
This item corresponds to the speech by Mr. Cesar Sandoval in Opening Week 1998 Industrial & Systems Engineering College of Engineers of Peru, highlighting the impact of the Asian crisis in the Peruvian industry.